Numerical Solution of Solid Mechanics Problems Using a Boundary-Only and Truly Meshless Method - Li, Xiaolin (Mathematical Problems in Engineering, 2012)
Combining the hybrid displacement variational formulation and the radial basis point interpolation, a truly meshless and boundary-only method is developed in this paper for the numerical solution of solid mechanics problems in two and three dimensions. In this method, boundary conditions can be applied directly and easily. Besides, it is truly meshless, that is, it only requires nodes generated on the boundary of the domain, and does not require any element either for variable interpolation or for numerical integration. Some numerical examples are presented to demonstrate the efficiency of the method.